When Study Abroad Is Not Enough: Improving Language Proficiency through Virtual Interaction - Christopher J. Jochum (The Advocate, 2016)
The purpose of this study was to investigate the experiences of an in-service Spanish teacher who, despite studying abroad on multiple occasions, was unable to meet the proficiency requirements necessary for professional licensure in her state. Using a single case study design (Yin, 2014), the author documented the year-long experiences of this teacher as she engaged in virtual language activities with a Native Spanish speaker to successfully improve her proficiency. The following paper will provide a brief overview of the study, the supporting theoretical framework, methods, results and scholarly contributions to the field of foreign language education and teacher preparation.